Hubungan Sinergi Antara Sekolah, Komite, Orangtua dan Masyarakat dalam Peningkatan Mutu Pendidikan - Fitri, Lidya; Asmendri, Asmendri (Lembaga Yasin AlSys, 2023)
School is an institution that moves and aims to improve the world of education. In its implementation, schools cannot stand alone, this agency really needs help from outside parties, including the Parents and Community Committee. A good school is a school that is able to foster good relations with all stakeholders both within the school environment and outside the school. The most influential relationship is the relationship between the school and the committee, parents and the community around the school. The existence of a synergistic relationship between these stakeholders is a major factor supporting the improvement of the quality of education. The purpose of writing this article is to see how far the influence of the relationship between schools, committees, parents and the community can affect quality improvement in a school)